Preparation method of heat-not-burn cigarette cooling material based on papermaking method

By using cooling materials of plant fiber-based paper and phase-change microcapsule coating prepared in HnB cigarette filters based on papermaking, the problem of easy softening and bonding of PLA sheets at high temperatures is solved, and more efficient flue gas temperature regulation and suction experience are achieved.

CN119686166AInactive Publication Date: 2025-03-25PRODUCTIVITY PROMOTION CENT OF PAPER IND +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411911014.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional HnB cigarette cooling materials such as PLA sheets are prone to soften and bond when high-temperature flue gas contact, resulting in blockage of flue gas channels and reducing the flue gas temperature regulation effect.

Method used

The preparation method based on papermaking method is adopted, and the base paper is prepared using plant fibers as the skeleton material, and the phase-change microcapsule powder is combined with polymer material to prepare a phase-change coating with excellent cooling performance, which is loaded on the surface of the base paper through the coating process.

Benefits of technology

It improves the structural stability and cooling effect of the material, avoids the softening and bonding problems of PLA sheets, significantly reduces the smoke temperature and improves the suction experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a preparation method of a heat-not-burn cigarette cooling material based on a papermaking method. The preparation method comprises the following steps: preparing base paper; and uniformly dispersing the phase-change microcapsules, the heat-conducting material and the phase-change water-soluble polymer material in water to obtain a mixed solution, coating two surfaces of the prepared base paper with the solution, and drying to obtain the heat-not-burn cigarette cooling material. The preparation method based on a papermaking method has the advantages of being simple and mature in process, suitable for large-scale production, low in cost and the like, the plant fibers serve as a framework in the composite material, the advantages that the paper base is combined with the phase change microcapsules are utilized, and the problems that a PLA film is large in brittleness, not resistant to processing and prone to melting and adhesion at the high temperature are effectively solved; the comprehensive performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a heat-not-burn cigarette cooling material based on a papermaking method, and belongs to pulping and papermaking, heat-not-burn cooling materials and heat-not-burn cigarettes. Background Art

[0002] Traditional cigarettes release more than 4,000 chemicals after being lit, of which about 70 have been proven to be carcinogenic. This hazard exists in both smokers and passive smokers. Quitting smoking can immediately reduce these hazards, but it is very difficult for people who are addicted to smoking to quit smoking. Therefore, various cigarette substitutes are widely available on the market. Among various new tobacco products, smokers can get the most similar oral / throat feeling and smoking ritual from HnB cigarettes as traditional cigarettes. HnB cigarettes use heating (200-400℃) instead of combustion (600℃) to distill and crack tobacco components to release smoke, which reduces the types and contents of harmful components compared to traditional cigarettes. However, this special way of generating smoke makes the amount and concentration of smoke released by HnB cigarettes relatively low, which makes this type of cigarette taste lighter. In order to improve the taste of the entrance, HnB cigarettes are usually short in length and have low smoke inhalation resistance, which makes the smoke entrance temperature higher. Therefore, choosing a suitable method to reduce the smoke temperature and ensure the smoke interception efficiency and smoking taste is of great significance to the development of short cigarettes. At present, the research on the cooling of HnB filter tips is mostly concentrated on the patents of various tobacco companies, but generally it is completed through the following two ways: one is to improve the cooling effect of smoke when passing through by designing a filter tip structure with a cooling effect; the other is to add heat absorbing materials, heat storage materials, heat conductive materials and other materials in the filter section to absorb heat, store and transfer heat, etc., to achieve the cooling of HnB cigarette smoke, but these cooling methods all have certain disadvantages. At present, polylactic acid (PLA) is commonly used as a new type of biodegradable cooling material. However, in the actual use of PLA sheets, it is found that after it contacts with high-temperature smoke and undergoes a glass transition, it will soften and bond. The thin sheet end that first contacts the smoke is severely adhered and collapsed, and even blocks the longitudinally extending smoke channel. The smoke no longer flows through the PLA sheet, reducing the contact area between the smoke and the cooling element, resulting in excessively high smoke temperature, excessive suction resistance, and smoke concentration. The quality of consumer smoking is reduced. Therefore, in order to solve such problems, the present technology utilizes papermaking technology to prepare a heating cigarette cooling composite material. The cooling material provided by the present invention is safe and environmentally friendly, has a simple preparation process, and has high cooling performance. It is applied to the cooling section of HnB cigarettes to replace the traditional PLA film cooling section, thereby improving the smoking experience of heat-not-burn cigarettes. Summary of the invention

[0003] In view of this, the object of the present invention is to provide a method for preparing a heat-not-burn cigarette cooling material based on a papermaking method. The present invention uses plant fibers as a skeleton material to prepare base paper, which significantly improves the structural stability of the material and makes it less likely to collapse when heated. At the same time, the phase change microcapsule powder is effectively combined with the phase change water-soluble polymer material to prepare a phase change coating with excellent performance. This coating is loaded on the surface of the base paper through a coating process, giving the paper good cooling performance. The phase change coating can absorb and store heat energy when the temperature is higher than the phase change point, thereby achieving temperature regulation of the cigarette paper filter when smoking. In addition, by utilizing the advantages of paper base combined with phase change microcapsules, the problems of PLA film's high brittleness, poor processing resistance, and easy melting and adhesion at high temperatures are effectively solved, thereby improving the comprehensive performance of the material.

[0004] In order to achieve the above object, the present invention mainly adopts the following steps:

[0005] The present invention provides a method for preparing a heat-not-burn cigarette cooling material based on a papermaking method, comprising the following steps:

[0006] (1) Preparation of base paper;

[0007] (2) Dispersing the phase change material in water to obtain a phase change coating having phase change properties, and coating the phase change coating on both sides of the prepared base paper surface with a coating amount of 8 to 20 g / m 2 After coating, the heat-not-burn cigarette cooling material is obtained by drying at a drying temperature of 85 to 105°C.

[0008] The method for providing base paper in step (1) comprises the following steps: mixing plant fibers with water, beating the fibers to obtain fiber slurry; adding a papermaking aid to the mixed slurry to obtain a mixed slurry; and papermaking the mixed slurry to obtain base paper.

[0009] The basis weight of the base paper is 40-70 g / m 2 , thickness is 0.03-0.10 mm, and tensile index is 60-85 N·m / g; the base paper is made from raw materials including plant fibers and papermaking additives; in the present invention, the plant fibers are preferably coniferous wood fibers and / or broadleaf wood fibers.

[0010] The beating degree of the fiber slurry is 40-60°SR. In the present invention, the mass concentration of the fiber slurry is 2-3wt%. In the present invention, when multiple types of fibers are used, the present invention preferably beats each type of fiber separately and then mixes them to obtain the fiber slurry.

[0011] The papermaking auxiliary agent is one or more of cationic starch, polyamide epichlorohydrin resin (PAE), and alkyl ketene dimer (AKD). The amount of cationic starch added in the auxiliary agent is 0.1-1.0% of the absolute dry fiber mass. The mass of PAE in the auxiliary agent is 0.1-1.0% of the absolute dry fiber mass. The mass of AKD in the auxiliary agent is 0.1-1.0% of the absolute dry fiber mass.

[0012] The mass concentration of the phase change coating in step (2) is 5 to 20%; the phase change material contained in the phase change coating includes one or more of polyvinyl alcohol (PVA), polyethylene glycol (PEG), phase change microcapsules, and thermal conductive materials; the glass transition temperature of the phase change material is 38 to 85°C.

[0013] The PVA contained in the phase change coating has a molecular weight of 50,000 to 200,000, and a mass concentration of the PVA of 2 to 10%, more preferably 2 to 5%.

[0014] The PEG contained in the phase change coating has a molecular weight of 2000-2500Da, and the mass concentration of the PEG is 2-10%, more preferably 2-5%.

[0015] The phase change temperature of the phase change microcapsules contained in the phase change coating is 38-52°C; the mass concentration of the phase change microcapsules is 2-20%, more preferably 5-10%; the phase change microcapsules are solid powder, are hydrophilic substances, can be dispersed in water, and their materials can be composed of esters, alcohols, hydrocarbons, inorganic substances, etc.

[0016] The heat-conducting material contained in the phase-change coating has the function of improving the heat transfer performance of the material. The heat-conducting material is one or more of nano-aluminum oxide and calcium carbonate. The mass concentration of the heat-conducting material is 2-10%, more preferably 2-5%.

[0017] The cooling material of the present invention forms a plurality of longitudinal channels parallel to the column axis of the filter rod in the heated cigarette filter in the form of curved folds.

[0018] The beneficial effects of the present invention are as follows:

[0019] 1. The present invention is a preparation method of a heat-not-burn cigarette cooling material based on a papermaking method, which has the advantages of simple and mature process, suitability for large-scale production, and low cost. Plant fibers are used as a skeleton in a composite material to solve the problem of easy melting and adhesion of PLA film at high temperature. Phase change microcapsules are added and coated to make the phase change microcapsules evenly distributed on the surface of the paper base, effectively improving the cooling effect of the material. Adding a thermal conductive material can accelerate the heat transfer effect of the cooling section, and a heat-not-burn cigarette cooling material with significant cooling effect and uniform performance distribution is prepared, which can be applied to the cooling section of HnB cigarettes to replace the traditional PLA film cooling section.

[0020] 2. The heat-not-burn cigarette cooling material of the present invention has a suitable phase change temperature (35-80°C) and a high phase change enthalpy (greater than 120 J / g), achieving efficient phase change heat absorption. The material has a higher phase change latent heat per unit mass. When used as a cigarette cooling material, it can effectively reduce the inlet and outlet temperatures, significantly alleviate the burning sensation of smoke on the oral cavity, and enhance the smoking experience. In addition, based on the performance requirements of the heat-not-burn cigarette filter, the phase change temperature of the phase change microcapsule can be flexibly adjusted, so that the material has stronger adaptability and customizability in the cooling application of the cigarette filter. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the relationship curve of the influence of ordinary heat-not-burn cigarettes (Ultra Plus) on the smoke temperature of the heat-not-burn cigarette filter.

[0022] Figure 2 This is a diagram showing the DSC test results of the cigarette cooling material used in Example 1.

[0023] Figure 3 This is the relationship curve of the effect of Example 1 on the smoke temperature of the heat-not-burn cigarette filter. DETAILED DESCRIPTION

[0024] The present invention will be further described in detail below in conjunction with specific implementation modes, but the embodiments do not limit the present invention in any form.

[0025] Comparative Example 1

[0026] (1) 50 parts by weight of softwood pulp was mixed with water and beaten using a disc refiner to obtain a softwood fiber pulp having a beating degree of 45° SR and a mass concentration of 2.0%;

[0027] 50 parts by weight of hardwood pulp was mixed with water and beaten using a disc refiner to obtain a hardwood fiber pulp having a beating degree of 50° SR and a mass concentration of 2.0%;

[0028] 0.8 weight part of cationic starch (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion, 0.2 weight part of PAE (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion; 0.3 weight part of AKD (calculated on an absolute dry weight) is prepared into an AKD aqueous dispersion;

[0029] The softwood fiber pulp, the hardwood fiber pulp, the reinforcing agent aqueous dispersion, the dispersant aqueous solution, and the AKD aqueous dispersion are mixed to obtain a mixed pulp with a solid content of 0.1 wt %, and the base paper is obtained after papermaking. The basis weight of the base paper is 70 g / m 2 , thickness is 0.075mm, and tensile index is 80.21N·m / g.

[0030] (2) Paper has no heat storage properties and cannot achieve the expected effect.

[0031] Comparative Example 2

[0032] (1) “Youjia” brand heat-not-burn cigarettes.

[0033] (2) The smoke temperature of the cigarette filter was tested using an electronic cigarette comprehensive test platform. The test results showed that the maximum inlet temperature was 50.15°C. Figure 1 shown.

[0034] Example 1

[0035] (1) 50 parts by weight of softwood pulp was mixed with water and beaten using a disc refiner to obtain a softwood fiber pulp having a beating degree of 45° SR and a mass concentration of 2.0%;

[0036] 50 parts by weight of hardwood pulp was mixed with water and beaten using a disc refiner to obtain a hardwood fiber pulp having a beating degree of 60° SR and a mass concentration of 2.0%;

[0037] 0.8 weight part of cationic starch (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion, 0.2 weight part of PAE (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion; 0.3 weight part of AKD (calculated on an absolute dry weight) is prepared into an AKD aqueous dispersion;

[0038] The softwood fiber pulp, the hardwood fiber pulp, the reinforcing agent aqueous dispersion, and the AKD aqueous dispersion are mixed to obtain a mixed pulp with a solid content of 0.1 wt %, and the base paper is obtained after papermaking. The basis weight of the base paper is 45 g / m 2 , thickness is 0.049mm, and tensile index is 67.83N·m / g.

[0039] (2) 3 parts by weight of PVA, 2 parts by weight of PEG, 5 parts by weight of 45° C. phase change microcapsule powder, and 2 parts by weight of calcium carbonate powder are uniformly dispersed in water to obtain a cooling paint with a mass concentration of 8.5%.

[0040] (3) Coat the cooling coating on both sides of the prepared base paper with a coating amount of 9 g / m 2 After coating, the cooling material is obtained by drying at 105°C.

[0041] (4) DSC curve of cigarette cooling material Figure 2 As shown, the results show that the phase change temperature of the cooling material in this embodiment is 44.7°C, the phase change enthalpy is 120.3J / g, it has a large endothermic peak, and strong endothermic capacity. In order to investigate the cooling performance of the composite filter rod, the smoking core material segment, hollow support segment and filter segment of the heated cigarette are retained, and only the cooling segment is replaced, and assembled into a test sample together with the filter segment. The heated cigarette smoking method used in the electronic cigarette comprehensive test platform is used to smoke the sample cigarette. The smoking program is set to a puff time of 2s per puff, one puff every 30s, and a puff capacity of (55.0±0.2)mL. A total of 11 puffs are smoked to test its performance. The test results show that compared with Comparative Example 2, the filter tip with added phase change material has a significant effect on reducing the smoke temperature. The maximum measured inlet temperature is 43.14°C, which has a good cooling effect. Figure 3 shown.

[0042] Example 2

[0043] (1) mixing 60 parts by weight of softwood pulp with water and beating the mixture using a disc refiner to obtain a softwood fiber pulp having a beating degree of 50° SR and a mass concentration of 2.0%;

[0044] 40 parts by weight of hardwood pulp was mixed with water and beaten using a disc refiner to obtain a hardwood fiber pulp having a beating degree of 50° SR and a mass concentration of 2.0%;

[0045] 0.8 weight parts of cationic starch (calculated on absolute dry weight) was prepared into a reinforcing agent aqueous dispersion, 0.3 weight parts of PAE (calculated on absolute dry weight) was prepared into a PAE aqueous dispersion; 0.3 weight parts of AKD (calculated on absolute dry weight) was prepared into an AKD aqueous dispersion.

[0046] The softwood fiber pulp, the hardwood fiber pulp, the reinforcing agent aqueous dispersion, the PAE aqueous dispersion, and the AKD aqueous dispersion are mixed to obtain a mixed pulp with a solid content of 0.1 wt %, and the base paper is obtained after papermaking. The basis weight of the base paper is 60 g / m 2 , thickness is 0.061mm, and tensile index is 77.81N·m / g.

[0047] (2) 4 parts by weight of PVA powder and 6 parts by weight of 45° C. phase change microcapsule powder are dispersed in water to obtain a cooling coating with a mass concentration of 7%.

[0048] (3) Coat the cooling coating on both sides of the prepared base paper with a coating amount of 8 g / m 2 After coating, the cooling material is obtained by drying at 105°C.

[0049] (4) The structure of the cigarette sample of this embodiment is the same as that of the cigarette sample in Example 1. The only difference is that the heat-not-burn cooling material provided in this embodiment is added to the cooling section. The maximum measured inlet temperature is 42.5°C, which has a better cooling effect.

[0050] Example 3

[0051] (1) mixing 40 parts by weight of softwood pulp with water and beating the mixture using a disc refiner to obtain a softwood fiber pulp having a beating degree of 50° SR and a mass concentration of 2.0%;

[0052] 60 parts by weight of hardwood pulp was mixed with water and beaten using a disc refiner to obtain a hardwood fiber pulp having a beating degree of 40° SR and a mass concentration of 2.0%;

[0053] 0.8 weight part of cationic starch (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion, 0.2 weight part of (PAE) (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion; 0.3 weight part of AKD (calculated on an absolute dry weight) is prepared into an AKD aqueous dispersion;

[0054] The softwood fiber pulp, the hardwood fiber pulp, the reinforcing agent aqueous dispersion, and the AKD aqueous dispersion are mixed to obtain a mixed pulp with a solid content of 0.1 wt %, and the base paper is obtained after papermaking. The basis weight of the base paper is 50 g / m 2 , thickness is 0.053mm, and tensile index is 70.65N·m / g.

[0055] (2) 3 parts by weight of PVA, 8 parts by weight of 40° C. phase change microcapsule powder, and 3 parts by weight of calcium carbonate powder are uniformly dispersed in water to obtain a cooling paint with a mass concentration of 6%.

[0056] (3) Coat the cooling coating on both sides of the prepared base paper with a coating amount of 7.5 g / m 2 After coating, the cooling material is obtained by drying at 105°C.

[0057] (4) The structure of the cigarette sample of this embodiment is the same as that of the cigarette sample in Example 1. The only difference is that the heat-not-burn cooling material provided in this embodiment is added to the cooling section. The maximum measured inlet temperature is 39.1°C, which has a better cooling effect.

[0058] Example 4

[0059] (1) mixing 60 parts by weight of softwood pulp with water and beating the mixture using a disc refiner to obtain a softwood fiber pulp having a beating degree of 45° SR and a mass concentration of 2.0%;

[0060] 40 parts by weight of hardwood pulp was mixed with water and beaten using a disc refiner to obtain a hardwood fiber pulp having a beating degree of 60° SR and a mass concentration of 2.0%;

[0061] 0.8 weight part of cationic starch (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion, 0.2 weight part of PAE (calculated on an absolute dry weight) is prepared into a PAE aqueous dispersion; 0.3 weight part of AKD (calculated on an absolute dry weight) is prepared into an AKD aqueous dispersion;

[0062] The softwood fiber pulp, hardwood fiber pulp, reinforcing agent aqueous dispersion, PAE aqueous dispersion, and AKD aqueous dispersion are mixed to obtain a mixed pulp with a solid content of 0.1 wt %, and a base paper is obtained after papermaking. The basis weight of the base paper is 40 g / m 2 , thickness is 0.041mm, and tensile index is 64.01N·m / g.

[0063] (2) 2 parts by weight of PVA, 5 parts by weight of 38°C phase change microcapsule powder, and 2 parts by weight of nano-alumina are uniformly dispersed in water to obtain a cooling paint with a mass concentration of 7%.

[0064] (3) Coat the cooling coating on both sides of the prepared base paper with a coating amount of 8.5 g / m 2 After coating, the cooling material is obtained by drying at 105°C.

[0065] (4) The structure of the cigarette sample of this embodiment is the same as that of the cigarette sample in Example 1. The only difference is that the heat-not-burn cooling material provided in this embodiment is added to the cooling section. The maximum measured inlet temperature is 37.7°C, which has a better cooling effect.

[0066] Example 5

[0067] (1) 50 parts by weight of softwood pulp was mixed with water and beaten using a disc refiner to obtain a softwood fiber pulp having a beating degree of 45° SR and a mass concentration of 2.0%;

[0068] 50 parts by weight of hardwood pulp was mixed with water and beaten using a disc refiner to obtain a hardwood fiber pulp having a beating degree of 40° SR and a mass concentration of 2.0%;

[0069] 0.8 weight parts of cationic starch (calculated by absolute dry weight) is prepared into a reinforcing aid aqueous dispersion, 0.2 weight parts of PAE (calculated by absolute dry weight) is prepared into an aqueous dispersion; 0.3 weight parts of (AKD) (calculated by absolute dry weight) is prepared into an AKD aqueous dispersion; 0.05 weight parts of organosilicon defoamer is prepared into a defoamer aqueous solution;

[0070] The softwood fiber pulp, hardwood fiber pulp, reinforcing agent aqueous dispersion, PAE aqueous dispersion, and AKD aqueous dispersion are mixed to obtain a mixed slurry with a solid content of 0.1 wt %, and a base paper is obtained after papermaking. The basis weight of the base paper is 70 g / m 2 , thickness is 0.089mm, and tensile index is 80.01N·m / g.

[0071] (2) Disperse 5 parts by weight of PVA and 5 parts by weight of 42° C. phase change microcapsule powder in water to obtain a cooling coating with a mass concentration of 6%.

[0072] (3) Coat the cooling coating on both sides of the prepared base paper with a coating amount of 7 g / m 2 After coating, the cooling material is obtained by drying at 105°C.

[0073] (4) The obtained heat-not-burn cigarette cooling material was used to prepare heat-not-burn cigarette samples, and its performance was tested. The test results showed that the filter tip with added phase change material had a significant effect on reducing the smoke temperature. The maximum measured inlet temperature was 41.5°C, which had a good cooling effect.

[0074] Example 6

[0075] (1) mixing 60 parts by weight of softwood pulp with water and beating the mixture using a disc refiner to obtain a softwood fiber pulp having a beating degree of 50° SR and a mass concentration of 2.0%;

[0076] 40 parts by weight of hardwood pulp was mixed with water and beaten using a disc refiner to obtain a hardwood fiber pulp having a beating degree of 45° SR and a mass concentration of 2.0%;

[0077] 0.8 weight part of cationic starch (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion, 0.2 weight part of PAE (calculated on an absolute dry weight) is prepared into a reinforcing aid aqueous dispersion; 0.3 weight part of AKD (calculated on an absolute dry weight) is prepared into an AKD aqueous dispersion;

[0078] The softwood fiber pulp, the hardwood fiber pulp, the reinforcing agent aqueous dispersion, and the AKD aqueous dispersion are mixed to obtain a mixed pulp with a solid content of 0.1 wt %, and the base paper is obtained after papermaking. The basis weight of the base paper is 40 g / m 2, thickness is 0.039mm, and tensile index is 62.92N·m / g.

[0079] (2) 2 parts by weight of PEG, 6 parts by weight of 45° C. phase change microcapsule powder, and 2 parts by weight of nano-alumina powder are uniformly dispersed in water to obtain a cooling coating with a mass concentration of 7.5%.

[0080] (3) Coat the cooling coating on both sides of the prepared base paper with a coating amount of 8.5 g / m 2 After coating, the cooling material is obtained by drying at 105°C.

[0081] (4) The structure of the cigarette sample of this embodiment is the same as that of the cigarette sample in Example 1. The only difference is that the heat-not-burn cooling material provided in this embodiment is added to the cooling section. The maximum measured inlet temperature is 44.1°C, which has a better cooling effect.

[0082] The heating cigarette cooling material prepared by Examples 1 to 6 can effectively reduce the smoke temperature, so that the temperature of the smoke entering the oral cavity after passing through the cooling material and the filter material is about 38 to 45°C. The cooling filter material has good mechanical processing performance, always keeps the longitudinal channel unobstructed, keeps the smoke flowing smoothly, and the smoke has a high aroma saturation, effectively improving the user's smoking experience.

[0083] The above description is combined with the accompanying drawings to describe the embodiments of the present invention, but the present invention is not limited to the above-mentioned specific implementation. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. The present invention provides a method for preparing a heat-not-burn cigarette cooling material based on a papermaking method, comprising the following steps: (1) Preparation of base paper; (2) Dispersing phase change microcapsules, thermal conductive materials, and phase change water-soluble polymer materials in water to obtain a mixed solution with phase change properties, and coating the solution on both sides of the prepared organic fiber-based paper at a coating amount of 8 to 20 g / m 2 After coating, it is dried at a temperature of 85-105°C to obtain a heat-not-burn cigarette cooling material.

2. The method for providing the base paper in step (1) according to claim 1 comprises the following steps: The plant fibers are mixed with water and pulped to obtain fiber pulp; A papermaking auxiliary agent is added to the fiber slurry to obtain a mixed slurry, and the mixed slurry is paper-made to obtain base paper.

3. The base paper according to claim 1 has a basis weight of 40 to 70 g / m 2 , thickness is 0.03~0.10 mm, and tensile index is 60~85 N·m / g; the base paper is made from raw materials including plant fibers and papermaking additives; in the present invention, the plant fibers are preferably coniferous wood fibers and / or broadleaf wood fibers.

4. The beating degree of the fiber slurry according to claim 2 is 40~60°SR, and the mass concentration of the fiber slurry is 2~3wt%; in the present invention, when multiple types of fibers are used, the present invention preferably beats each type of fiber separately and then mixes them to obtain fiber slurry.

5. The papermaking auxiliary agent according to claim 2 is one or more of cationic starch, polyamide epichlorohydrin resin (PAE), and alkyl ketene dimer (AKD); the amount of cationic starch added in the auxiliary agent is 0.1-1.0% of the absolute dry fiber mass; the mass of PAE in the auxiliary agent is 0.1-1.0% of the absolute dry fiber mass; the mass of AKD in the auxiliary agent is 0.1-1.0% of the absolute dry fiber mass.

6. According to claim 1, the mass concentration of the mixed solution in step (2) is 5-20%; the phase-change water-soluble polymer material comprises one or more of polyvinyl alcohol (PVA) and polyethylene glycol (PEG); and the phase change temperature of the phase-change water-soluble polymer material is 38-85°C.

7. The phase change coating according to claim 6 contains PVA with a molecular weight of 50,000 to 200,000, and the mass concentration of polyvinyl alcohol is 2 to 10%, more preferably 2 to 5%.

8. The phase change coating according to claim 6 contains PEG, the molecular weight of which is 2000-2500Da, and the mass concentration of PEG is 2-10%, more preferably 2-5%.

9. The phase change temperature of the phase change microcapsules contained in step (2) according to claim 1 is 38-52°C; the mass concentration of the phase change microcapsules is 2-20%, more preferably 5-10%; the phase change microcapsules are solid powder, are hydrophilic substances, can be dispersed in water, and their materials can be composed of esters, alcohols, hydrocarbons, inorganic substances, etc.

10. The thermally conductive material contained in step (2) according to claim 1 is one or more of nano-alumina and calcium carbonate; the mass concentration of the thermally conductive material is 2-10%, more preferably 2-5%.

Citation Information

Patent Citations

  • Cooling material for heat-not-burn cigarette and preparation method thereof

    CN111838752A

  • Phase change film based on phase change microcapsules and preparation method

    CN116200087A